2013
DOI: 10.1111/joor.12073
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying rate in subjects with malocclusion examined by [13C] breath test

Abstract: Masticatory function is significantly lower in individuals with malocclusion than in those with normal occlusion. Although several studies suggest that masticatory function influences gastrointestinal digestive function, the relationship between malocclusion and gastrointestinal symptoms has not been studied extensively. We hypothesised that insufficient masticatory function would increase the functional burden of the stomach and have some influence on the gastrointestinal system. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Rabbit dental pathology can lead to lesions of the mouth, pain, difficulty chewing food e.g. avoidance of, or prolonged chewing of, hard foods as seen in bears with dental pathology 42 , and possibly gastrointestinal problems following inadequately chewed food as found in humans 43, 44 , among other issues described earlier. The rescue staff caring for rabbits in the current study were more knowledgeable of and attentive to rabbit health issues than many owners, and health records indicated that they had already identified more dental issues requiring veterinary attention in lop-eared than erect-eared rabbits, before our study started.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit dental pathology can lead to lesions of the mouth, pain, difficulty chewing food e.g. avoidance of, or prolonged chewing of, hard foods as seen in bears with dental pathology 42 , and possibly gastrointestinal problems following inadequately chewed food as found in humans 43, 44 , among other issues described earlier. The rescue staff caring for rabbits in the current study were more knowledgeable of and attentive to rabbit health issues than many owners, and health records indicated that they had already identified more dental issues requiring veterinary attention in lop-eared than erect-eared rabbits, before our study started.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on 11 normal occlusion females and 11 malocclusion females noticed a significant relationship between malocclusion and gastric emptying function. This could be due to increased functional burden on stomach due to inferior activity of masticatory muscles in the malocclusion patients [57] causing inadequate mastication of food in the oral cavity.…”
Section: Association Between Skeletal Malocclusion and Other Medical mentioning
confidence: 99%
“…Since then, the effect of chewing on the function of the digestive system has been widely studied but the association was still inconclusive. [2][3][4][5][6][7][8] This may be related to the variations of subjects, test foods and gastric function test methods. The study of a direct association between masticatory performance and gastric function might help to reconcile the previous findings.…”
mentioning
confidence: 99%